Keanekaragaman Genus Serangga Air sebagai Bioindikator Kualitas Perairan - Manap Trianto; Nuraini Nuraini; Sukmawati Sukmawati; Moh Dahri Kisman (Unversitas Muhammadiyah Mataram, 2020)
Abstract: Aquatic insects are groups of insects that most of their life in the water body. Aquatic insects are part of macrozoobenthos. Aquatic insects are very important roles in the ecological system due to various reasons. Insects are bio-indicators of water in water bodies such as rivers. The aims of the study were to determine the diversity and the potential roles of aquatic insects in the Kali Batu Anyar ecosystem. The research method used purposive random sampling method. The sampling of the data was conducted by Surber nets. The samples obtained were identified and analyzed using the Shannon-Wiener index. The result consist of 6 Orders, 10 Families and 4 Genus were founded. According to the Shannon-Wiener diversity index of (H'), the diversity of aquatic insects in the upper Kali Batu Anyar was higher than the bottom part of the river with value of H’ was 3,6. By using SIGNAL 2 grade, Order Ephemeroptera, Trichoptera and Coleoptera were grouped to be very sensitive and a sensitive insect therefore those can be used as indicator for water quality. It can be concluded that Kali Batu Anyar was in good water conditions.Abstrak: Serangga air merupakan kelompok serangga yang sebagian hidupnya berada di badan air. Serangga air termasuk dalam makrozoobentos. Serangga air sangat penting dalam sistem ekologi karena berbagai alasan. Serangga air adalah bioindikator dalam badan air seperti sungai. Tujuan Penelitian ini untuk mengetahui keanekaragaman dan potensi peranan serangga air di ekosistem. Peneltian menggunakan metode Purposive Random Sampling. Pengambilan sampel menggunakan jaring Surber. Sampel yang diperoleh diidentifikasi dan dianalisis menggunakan indeks Shanon Wiener. Serangga air yang diperoleh di kelompokan pada 6 Ordo terbagi dari 10 Famili dan 4 Genus. Indeks keanekaragaman Shanon-Wiener H’ : 3,6 menunjukan keanekaragaman serangga air yang tinggi di hulu kali Batu Anyar tinggi. Berdasarkan SIGNAL 2 grade, serangga air anggota Ordo Ephemeroptera, Trichoptera dan Coleoptera yang ditemukan bersifat sangat sensitif dan sensitif dapat digunakan sebagai indikator kualitas air. Kali Batu Anyar dalam kondisi perairan yang baik.